Analisa Penyebab Kepatuhan Penandaan Lokasi Operasi dan Penjadwalan Operasi Elektif Terhadap Ketepatan Operasi (Studi Kasus di Instalasi Kamar Bedah RS KSH Tayu Pati Jawa Tengah) - Budijono, Rudy; Yaniawati, Poppy; Restiani Widjaja, Yani (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2024)
One of the hospital's duties is to provide services in accordance with patient safety. These include marking operation locations and scheduling elective operations. KSH Tayu Pati Hospital experienced a decline in achieving indicators for marking operation locations and scheduling elective operations. This can have an impact on the accuracy of carrying out operations. Therefore, this research will look at the effect of compliance with marking operation locations and scheduling elective operations at KSH Tayu Pati Hospital. This research uses a mix method with the help of SPSS calculations and in-depth interviews. This research used a sample of 33 respondents consisting of all doctors and IBS officers at KSH Tayu Pati Hospital. The result is that compliance with marking the operation location has an influence (sig. 0.001 < 0.05) on the accuracy of the operation. And compliance with elective surgery scheduling has an influence (sig. 0.001 < 0.05) on the accuracy of the operation. However, there are many aspects that must be improved at KSH Tayu Pati East Java Hospital, including continuing to refresh the knowledge and attitudes of doctors and staff at IBS at KSH Tayu Pati East Java Hospital.